EL APOSTOLADO DE LA PRENSA LA ACTUACIÓN DEL SALESIANO BERNARDO GENTILINI - Loyola Tapia, Manuel (2012)
During the first third of the twentieth century, the Chilean Catholic Church promoted the evangelical proyect of the Godd Press. Among the various actions and iniciatives that this involved, those undertaken buy presbyter Bernardo Gentilini constituted one of the most prominent. Based on primary sources, we present here a general countenance of his performance as propagandist of the Good Press, one of the inaugural moments of the mass media in Chile.